2009
DOI: 10.1248/bpb.32.558
|View full text |Cite
|
Sign up to set email alerts
|

The Construction and Characterization of Self-Sufficient Lanosterol 14-Demethylase Fusion Proteins Consisting of Yeast CYP51 and Its Reductase

Abstract: Cytochrome P450 (P450) is a group of heme-protein monooxygenases that catalyze the oxidation of a wide variety of organic compounds including steroids, fatty acids, xenobiotics, and so forth. P450 requires two electrons to activate one oxygen molecule in its catalytic cycle, and the electrons are provided from reduced nicotinamide-adenine dinucleotide phospahte (NADPH) or reduced nicotinamide-adenine dinucleotide (NADH) by means of a specific electrontransferring system, such as NADPH-P450 reductase (P450 redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…The modeling experiments suggested that lanosterol could fit into the active site, as supported by the type I binding spectra, but could not orientate viously calculated K s value of 11 M for eburicol binding to MgCYP51 by UV-visible spectroscopy (16) suggesting that the K m value is not solely dependent on the affinity of MgCYP51 for substrate. The MgCYP51 K m value for eburicol was comparable with that determined for human CYP51 of 30 M with lanosterol (30) but was 4-to 6-fold larger than K m values previously determined for C. albicans and S. cerevisiae CYP51 enzymes (15,31,32), suggesting a degree of variability with regard to substrate affinity among CYP51 enzymes.…”
Section: Discussionsupporting
confidence: 69%
“…The modeling experiments suggested that lanosterol could fit into the active site, as supported by the type I binding spectra, but could not orientate viously calculated K s value of 11 M for eburicol binding to MgCYP51 by UV-visible spectroscopy (16) suggesting that the K m value is not solely dependent on the affinity of MgCYP51 for substrate. The MgCYP51 K m value for eburicol was comparable with that determined for human CYP51 of 30 M with lanosterol (30) but was 4-to 6-fold larger than K m values previously determined for C. albicans and S. cerevisiae CYP51 enzymes (15,31,32), suggesting a degree of variability with regard to substrate affinity among CYP51 enzymes.…”
Section: Discussionsupporting
confidence: 69%
“…The absolute spectra of AF51B in the presence and absence of 70 M lanosterol indicated that a less than 1% change in spin state had occurred. The K s value obtained for lanosterol was comparable to the K m value of 7.4 M for lanosterol reported for C. albicans CYP51 in metabolism studies (39) but 2-fold higher than the K m value for S. cerevisiae CYP51 (20). Further investigations are required to fully characterize the substrate binding specificity of AF51B.…”
Section: Vol 54 2010supporting
confidence: 73%
“…For the same purpose, Ncp1 and its redox partner Erg11, a lanosterol 14‐alpha‐demethylase that belongs to the cytochrome P450 family (Aoyama et al ., 1996), were fused as a single protein. The enzymatic reduction of Erg11 was faster in the purified fusion protein than in the reconstituted complex, due to electron transfer occurring both inter‐ and intra‐molecularly (Kitahama et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%